Penerapan Metode Discovery Learning untuk Meningkatkan Aktifitas Belajar dan Hasil Belajar Desain Grafis Percetakan pada Siswa - I Gusti Ngurah Bagus Aryotejo (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2020)
The purpose of this study was to determine the application of discovery learning methods to improve learning activities and learning outcomes Graphic Design Printing Material Picture Forms and Perspectives One-Point Missing Class XI Students of SMK Negeri I Tampaksiring Academic Year 2019/2020. This research is a class action research (Classroom Action Research). The study was conducted in class XI of Tampaksiring I Public Vocational School which was conducted from June to August 2019. Based on the results of the study showed that the application of discovery learning method can improve learning activities and learning outcomes of graphic design printing data material normally distributed Class XI SMK Negeri 1 Tampaksiring 2019-2020 Academic Year. This is indicated by 1) increasing each cycle in the pre-activity cycle of students obtained a percentage of 41% included in the unfavourable category, in cycle 1 the percentage of student activity increased to 72% included in the sufficient category and in the second cycle the process increased to be better by 89% included in either category. 2) Increased student learning outcomes in the pre-cycle stage, Cycle I, and Cycle II increased learning outcomes. In the pre-cycle stage, from 33 students, data obtained that there were 25 students or 76% who scored less than the cut-off score is 75 and 8 students or 24% whose scores were more than the cut-off score is 75 with an average value of 64.84. Furthermore, the first cycle of 33 students obtained data that there were 13 students or 39% who received grades less than the cut-off score is 75 and 20 students or 61% whose values ​​were more than the cut-off score is 75 with an average value of 70.69, and in the second cycle from 33 students obtained data that there are 4 students or 12% who scored less than the cut-off score is 75 and 29 students or 88% whose value was more than the cut-off score is 75 with an average value of 77.42.